Interior of the mandapa (pillared hall) of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Pictured here is a view of the interior of the mandapa (pillared hall) of Neelkanth Mahadev Temple as seen from the northwestern corner of the mandapa. The tri-kuta (triple-shrine) temple has a shared mandapa which is in front of all three shrines. The mandapa has four pillars at the centre. All the exterior walls of the mandapa have been haphazardly covered.